La persona jurídica como responsable penal ante el proceso (Acta Judicial Journal, 2018)
This paper deals with the role of the legal entity on the criminal proceeding, pointing out the most transcendental situations of the suspect legal person, from the first appearance to the trial. All of this is analyzed along the different stages of the criminal proceedings: appearance, deposition, possible acceptance of charges and possible failure to appear, paying special attention on the precautionary measures concerning the legal entity.
Keywords: Legal entity/legal person, Compliance, Precautionary measure, Deposition, Trial, Acceptance of charges, Investigation, Failure to appear, Default